Carnal Crimes: Sexual Assault Law in Canada, 1900-1975 - Janovicek, Nancy (Labour / Le Travail, 2009)
The article reviews the book, "Carnal Crimes: Sexual Assault Law in Canada, 1900-1975," by Constance Backhouse.
Keywords: BACKHOUSE; Constance; BOOKS – Reviews; CARNAL Crimes: Sexual Assault Law in Canada 1900-1975 (Book); Nonfiction; RAPE – Law & legislation – History